Systemic Effects of Hemorrhagic Snake Venom Metalloproteinases: Untargeted Peptidomics to Explore the Pathodegradome of Plasma Proteins - Luciana Bertholim (MDPI AG, 2021)
Hemorrhage induced by snake venom metalloproteinases (SVMPs) is a complex phenomenon that involves capillary disruption and blood extravasation. HF3 (hemorrhagic factor 3) is an extremely hemorrhagic SVMP of Bothrops jararaca venom. Studies using proteomic approaches revealed targets of HF3 among intracellular and extracellular proteins. However, the role of the cleavage of plasma proteins in the context of the hemorrhage remains not fully understood. The main goal of this study was to analyze the degradome of HF3 in human plasma. For this purpose, approaches for the depletion of the most abundant proteins, and for the enrichment of low abundant proteins of human plasma, were used to minimize the dynamic range of protein concentration, in order to assess the proteolytic activity of HF3 on a wide spectrum of proteins, and to detect the degradation products using mass spectrometry-based untargeted peptidomics. The results revealed the hydrolysis products generated by HF3 and allowed the identification of cleavage sites. A total of 61 plasma proteins were identified as cleaved by HF3. Some of these proteins corroborate previous studies, and others are new HF3 targets, including proteins of the coagulation cascade, of the complement system, proteins acting on the modulation of inflammation, and plasma proteinase inhibitors. Overall, the data indicate that HF3 escapes inhibition and sculpts the plasma proteome by degrading key proteins and generating peptides that may act synergistically in the hemorrhagic process.